BOOK DOOMSDAY: THE MARCH OF PROGRESS AND THE FATE OF THE BOOK. - POTTS, JOHN (Meanjin)
This essay considers cloud technology as the future of reading. It has been predicted that the last newspaper will be seen in the presses in 2043. The cloud is the immaterial zone, the datasphere in which digital words, images and sounds reside. Cloud will dispense of turning trees into paper, of books gathering dust at home. A portable, stylish device will reportedly bring the cloud technology down to the reader.